PRODUKSI BIOETANOL DARI KULIT PISANG MELALUI HIDROLISIS ASAM SULFAT [The Production of Bioetanol from Banana Peel Trough Sulphuric Acid Hidrolisis] - Asih Sukowati; Sutikno Sutikno; Samsul Rizal (Jurnal Teknologi & Industri Hasil Pertanian, 2014)
Banana fruit is one of main product of Lampung Province. Banana is commonly utilized as raw material of banana chip production and its peel can be converted into bioethanol. The Objectives of this study were to find out the optimum treatments of  hydrolysis and fermentation for producing bioetanol.  Two steps, namely  hydrolysis and fermentations, were carried out in this study. In the hydrolysis step, two treatments - H2SO4 consentration and hydrolysis duration – were implemented.  The H2SO4 concentration treatment consisted of five level (0, 0.025, 0.050, 0.075, and 0,100 M); and the hydrolysis period treatment consisted of two level (15 dan 30 minutes). Bioethanol fermentation was carried out at room temperature for 72 hours with Saccharomyces cerevisiae as starter at concentration of 0%, 5%, 10%, and 15% (w/v).  The treatments were arranged in Randomized Complete Block Design (RCBD) with three replications.  Before and after hydrolysis, the cellulose, hemicellulose, and lignin contents of  banana peel were determined. The reducing sugar concentrations were measured after hydrolysis, and bioethanol concentrations were measured after fermentation. The  data of the cellulose, hemicellulose, lignin, reduced sugar, and bioethanol were tabulated and analyzed descriptively.  The results of this study showed that the optimum treatment for hydrolysis was H2SO4 solution at a concentration of 0.050 M at 1210C for 15 minutes.  The treatment yielded reduced sugar at a concentration of 11,26mg/100 mL.  The optimum treatment for fermentation was a starter concentration of 10% (w/v) which produced bioethanol at a concentration of 0.03% (v/v). Keywords : banana peel, bioethanol, hydrolysis, H2SO4, reducing sugar.